Evaluation of N-alkanes as Faecal Markers to Estimate Diet Composition, Feed Intake, and Digestibility in European Bison (Bison bonasus). (31st October 2022) - Mendes Ferreira, Luis Miguel; Pereira, Daniela; Lourenço, Ana; Rodrigues, Miguel
Abstract : There is a lack of knowledge on the European bison ( Bison bonasus L . 1758) foraging behavior that is essential to develop an appropriate feeding strategy for each specific situation (captive or wild). Utilization of faecal markers may allow us to fill this gap, accommodating animal welfare and intensive labour issues that are major limitations of traditional techniques. This study aimed to evaluate the potential of n -alkane markers (C25 to C33 ) to estimate diet composition, feed intake its digestibility on three captive male Bison bonasus fed on known amounts of straw, and a beeswax labelled concentrate feed. Feeds and faecal samples were taken daily during 10 days. Prior to calculations, faecal concentrations were corrected for incomplete faecal recovery (FR). Results indicated that 4–5 days were sufficient for these markers to reach a steady concentration in bison faeces. Accurate estimates of diet composition and feed intake were obtained not differing from known values. Results suggest that faecal recovery of n -alkanes in bison are incomplete and tend to increase with carbon-chain length. Apparent dry-matter digestibility (DMDap) estimates were affected by the n-alkane (C27, C29, C31, and C33 ) used in the calculations. Estimates of DMDap obtained with application of FR corrections were 6.3% higher than those without correction. Results indicate that feeding a known amount of beeswax labelled supplement can be successfully used to estimate composition, feed intake, and its digestibility, requiring the application of n-alkane FR data.